ANALISIS PENERAPAN PAJAK PENGHASILAN PP 46 TAHUN 2013 PADA USAHA MIKRO KECIL MENENGAH - Dewi Saptantinah Puji Astuti, Arifatul Istifarah, Fadjar Harimurti & (Universitas Slamet Riyadi, 2018)
This study aims to to know understanding PP 46 year 2013 and application of the calculation, payment and reporting income tax at a venture micro small medium enterprises case study Mat Moen tavern in Boyolali. This research analyze the calculation, payment and reporting income tax on Mat Moen tavern based on government regulation no 46 in 2013. Descriptive analysis was used in the study to find out in a direct the application of PP 46 Year 2013 by analyzing the power obtained from research object. Understanding Mat Moen tavern calculated on the basis of the questionnaire that it is processed using a scale Guttman.The data which used in research note this is the gross sales every month, payment evidence and reporting taxes for one year the tax. Based on the research done understanding tavern mat moen against the implementation of pp 46 2013 shows decided how much 77% it means understand against PP 46 in 2013. The study aimed to identify the pp 2013 and application of the 46 years, income tax payment and reporting on micro small medium enterprises case study Mat Moen tavern in Boyolali. This study analyzing the income tax payment and reporting on Mat Moen tavern based on PP 46 year 2013. This study using analysis descriptive heading for directly know the real application of PP 46 year 2013 by analyzing its resources obtained from the research. Understanding the malt shop tax carried out by moen 2013 46 years according to government regulation. Depositing tax using e-billing system which delivered at the post office and atm. Tax reporting done manually by filling out reported to the tax office.Keywords: PP 46 Year 2013, micro small and medium enterprises, understanding, calculation, depositing, reporting